Diálogo de voces : Nuevas lecturas sobre la obra de María Rosa Lojo - Crespo Buiturón, Marcela; Crespo Buiturón, Marcela (Book collections on Project MUSE., 2018)
This volume, made up of eight essays and a kind of epilogue in dialogue with the writer Maria Rosa Lojo, discusses some of the backbones of her work: the conflictive relationship with the sacred and its constant interpellation, the memory of immigration, the presence of female figures questioning the hegemonic male discourse or other marginal characters who resignify official history, the always questionable and questionable autobiographical features in his work from parental figures or a possible mapping of intimacy, the identity problem through the characters that are located on a suspicious edge between two worlds and the harmonious meeting of different aesthetics, discourses and genres within their works.